2020
DOI: 10.1016/j.ecns.2020.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Nursing Video Consultations: An Innovative Proposal During Covid-19 Confinement

Abstract: Background: In response to the closure of universities and the canceling of in-person classes due to the COVID-19 pandemic, this study was designed to focus on a solution for adapting simulation-based education to this situation. Method: A mixed study was conducted to analyze nursing students' satisfaction and perceptions (n ¼ 48) about simulated nursing video consultations. Results: Nursing students expressed a high level of satisfaction and positive perceptions about this innovative proposal. Conclusions: Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 35 publications
(61 reference statements)
6
46
1
7
Order By: Relevance
“…Another study indicated that frequent practice is needed to maintain CPR skills [ 28 ]. There are several recent investigations that coincide with our results, affirming that clinical simulation is an essential component in nursing education [ 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another study indicated that frequent practice is needed to maintain CPR skills [ 28 ]. There are several recent investigations that coincide with our results, affirming that clinical simulation is an essential component in nursing education [ 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…The 2015 American Heart Association (AHA) Guidelines include recommendations for BLS training such as simulations [ 15 , 21 , 22 ] using high-fidelity manikins, feedback devices, more frequent training, and online courses [ 15 ] as resources to teach and learn CPR skills in continuing education [ 23 , 24 ]. Various sources confirm that clinical simulation is an essential component of nursing education [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…A high-fidelity clinical simulation scenario depicting a potential case of GBV during COVID-19 confinement was performed in the form of a simulated video consultation. This methodology is considered as one more online high-fidelity simulation teaching option [ 42 , 43 ]. Therefore, it was carried out using a virtual platform for online video conferences provided by the university, namely Blackboard Collaborate LauncherTM.…”
Section: Methodsmentioning
confidence: 99%
“…All of the interviews were recorded with the participant’s verbal consent. Lastly, a pilot study was not necessary, as indicated in a similar study that was previously conducted to evaluate the nursing students’ perceptions in other clinical situations [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation